A study of an aftermarket voltage stabilizer for its performance and emission on passengers vehicle - Mohiuddin, A. K. M.; Ihsan, Sany Izan; Abd Murat, Noor Azammi (IIUM Press, 2011)
Heavy electrical load in a vehicle will consume more electrical power from the battery. Thus \vilt affect the performance of the vehicle and voltage stabilizer is created to cater this problem. This chapter shows the experimental investigation of the performance and the emission effect the vehicle using aftermarket voltage stabilizers. The experiment is mostly carried out in laboratory and few experiments were carried out by test drive. All data are recorded compared \vith the data found from the MATLAB analysis. Chassis dynamometer test shows on certain value of capacitors it does have an increase of torque and power by 5%. From emission result by using Gas Analyzer, it shO\vs that the voltage stabilizer could reduce some the hazardous gases especially hydrocarbon which contributes to the global warming. consumption from 160 km test drive shows a 5% mileage increase from the ordinary vehical setting. From all experiments conducted, the best capacitor value needed to be equipped ill voltage stabilizer is between 100 mF to 120 mF using 16 volt or 25 volt. With a proper value capacitors size, the authors hope this voltage stabilizer can be equipped in all consumer vehical for good engine performance, better mileage and most importantly to reduce global wannin~ producing less harmful emissions.